2006
DOI: 10.1002/bit.20809
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐scanning lithography (LSL) for the soft lithographic patterning of cell‐adhesive self‐assembled monolayers

Abstract: We report the development of laser-scanning lithography (LSL), which employs a laser-scanning confocal microscope to pattern photoresists that can be utilized, for example, in the fabrication of masters for use in soft lithography. This convenient technique provides even exposure across the entire view field and facilitates accurate alignment of successive photoresist exposures. Features on the scale of 3 microm have been achieved to date with a 10x objective (NA 0.45). Virtual masks, instructions for laser ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 32 publications
0
49
0
Order By: Relevance
“…Images created in a personal computer were projected through LCDP onto photoreactive samples, and EC adhesion was restricted to capillary vessel-like networks patterned onto the substrates [54]. An alternative method of photolithography employing conventional confocal microscope system was recently reported [55,56]. Virtual patterns were generated in a confocal scanning software, and photoreactive substrates including photoresists and PEG hydrogels were exposed to the confocal lasers as outlined by the virtual patterns with micron scale resolution easily achieved.…”
Section: Micropatterning Techniques To Regulate Angiogenesis-micropatmentioning
confidence: 99%
“…Images created in a personal computer were projected through LCDP onto photoreactive samples, and EC adhesion was restricted to capillary vessel-like networks patterned onto the substrates [54]. An alternative method of photolithography employing conventional confocal microscope system was recently reported [55,56]. Virtual patterns were generated in a confocal scanning software, and photoreactive substrates including photoresists and PEG hydrogels were exposed to the confocal lasers as outlined by the virtual patterns with micron scale resolution easily achieved.…”
Section: Micropatterning Techniques To Regulate Angiogenesis-micropatmentioning
confidence: 99%
“…Grooves have been introduced usually by lithographic macro- or nanofabrication techniques on synthetic substrates such as glass, [34] metals, [35] poly(dimethylsiloxane) (PDMS), [36] and nondegradable synthetic polymers [16,37] to understand cell behavior on the patterned surfaces, but without consideration of the biological compatibility and direct tissue utility of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this research showed that the introduction of laminin on the micro-patterned substrate gave rise to an enhancement of cell orientation, elongating them further when compared to solely using the micro-patterned surface. Cell orientation and distribution, and how biological adhesion can be affected using lithography techniques, was also confirmed by Miller et al [103]. In addition to cell adhesion modulation, it was also commented that nano-machining with lithography could be applied to cell transfection and drug delivery [93], two areas of extreme in importance within the healthcare industry.…”
Section: Lithographymentioning
confidence: 78%